Screening and characterization of bacterial skin and soft tissue infections for outpatients from two different geographical and social areas - Mohamed Hassan Hussein Ahmed; Ola Hamouda Ibrahim; Youssef A. Mawgoud (Cairo : Mohamed Hassan Hussein Ahmed, 2021)
This investigation aimed to the study of variations of skin and soft tissue infections (SSTIs) bacteria from two different geographical and social areas (Sharm El-Sheikh and El-Sheikh Zaid) and their response to some commonly antibiotics. The numbers of infected patient were higher in El- Sheikh Zaied 68% (34 of 50 patient) compared with Sharm El- Sheikh City 48% (21 of 50 patient), and the infected females were more than males in both cities. Screening and identification of isolated pathogenic bacteria based on morphological, biochemical and molecular biology techniques. PCR using 16S rRNA primer was conducted to emphasize the morphological, biochemical and genetical differences between isolates belonging to the same genus in both areas. It was found that there were marked diversity in numbers and species of isolated bacteria, 21 pathogenic bacteria isolated and identified from Sharm El- Sheikh; it was included 7 staphylococcus aureus, 7 klebseilla spp., 4 pseudomonas spp. and 3 E.coli. Thirty four pathogenic bacteria from El-sheikh Zaied; it was included 10 klebseilla spp., 9 pseudomonas spp., 6 Acinetobacter spp., 3 E.coli, 3 Proteus spp., 2 staphylococcus aureus and just one isolate Morganella morganii. It was found that Imipenem, Piperacillin/Tazobactam and Meropenem were the most effective antibiotics against Gram-negative bacteria isolated from both areas, while Azithromycin, Cephalothin, Linezolid, Amikacin and Vancomycin were the most effective antibiotics against Gram-positive bacteria isolated from both areas
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Botany and Microbiology
Issued also as CD
Keywords: Bacterial skin; Geographical and social areas; Soft tissue infections